To change the equation \(2x + 3y = 1470\) into slope-intercept form (which is generally written as \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept), we need to solve for \(y\).
Here are the steps:
-
Start with the original equation: \[ 2x + 3y = 1470 \]
-
Subtract \(2x\) from both sides to isolate the term with \(y\): \[ 3y = -2x + 1470 \]
-
Now, divide every term by 3 to solve for \(y\): \[ y = -\frac{2}{3}x + \frac{1470}{3} \]
-
Simplify \(\frac{1470}{3}\): \[ \frac{1470}{3} = 490 \]
-
Now we can write the equation in slope-intercept form: \[ y = -\frac{2}{3}x + 490 \]
Identifying the slope and y-intercept:
- The slope \(m\) is \(-\frac{2}{3}\).
- The y-intercept \(b\) is \(490\).
Summary:
- The equation in slope-intercept form is: \[ y = -\frac{2}{3}x + 490 \]
- Slope (\(m\)): \(-\frac{2}{3}\)
- y-intercept (\(b\)): \(490\)